Healthcare Professionals' Perspectives on Dignity in Dementia: A Qualitative Analysis - Frederik Schou-Juul; Rebecca Amalie Struwe Kjeldsen; Lucca-Mathilde Thorup Ferm; Sigurd Lauridsen (SAGE Publishing, 2024)
In dementia care, the concept of dignity has garnered substantial attention from both researchers and policymakers. However, the concept often remains vague and open to interpretation, potentially leading to misunderstandings and suboptimal care for people with dementia. As healthcare professionals occupy a critical role in upholding dignity, exploring their viewpoints on this complex concept is paramount. In this study, we explore Danish healthcare professionals' views on the dignity of people with dementia and discuss these perspectives against existing theoretical accounts. We employed thematic analysis of data collected during facilitated discussions with a total of 99 healthcare professionals, including nurses and healthcare workers, during which we posed the question, "What is dignity to you?" and documented their perspectives. Through a systematic process of data coding and interpretation, we identified recurring patterns in their responses. This approach allowed us to uncover the depth and complexity of their viewpoints, providing valuable insights into the multifaceted nature of dignity as perceived by healthcare professionals. Our findings revealed that healthcare professionals possessed a nuanced understanding of dignity, recognizing both a subjective element and a universal aspect applicable to all individuals, aligning with theoretical interpretations. However, conceptual ambiguity remained a challenge.